The Effect Of Percentage Of Asphalt Mixed Recycling Materials On Characteristics Of Mechanical Mixed Heat Asphalt AC – WC (Achalt Concrete - Wearing Course) - Ramadhan, Sofyan; Diana, I Wayan; Putra, Sasana (Universitas Lampung, 2019)
Handling road damage using the greenroads method is one solution to the problem of natural resources. This method uses a recycling method of dismantling the old pavement layers to be used as a mixture of new pavement layers. This study aims to determine the use of Reclaimed Asphalt Pavement (RAP) material as a mixture of materials to be used again as AC - WC (Asphalt Concrete - Wearing Coarse) pavement and determine the best percentage between recycled asphalt mixture from RAP and new material. The results of this study were obtained for the stability value on the use of 25% RAP, 50% RAP and 75% in a row obtained 1300,320 kg, 1076,468 kg and 966 kg. Of the three variations in the use of RAP it has mixed characteristics and marshall characteristics that meet the General Specifications of Bina Marga. The Optimum Asphalt Content (KAO) value for the percentage of RAP use of 25%, 50% and 75% in a row obtained 5,8%, 5,6% and 5,4%. The higher the use of RAP percentage, the Optimum Asphalt Level (KAO) obtained is getting smaller. Keyword: RAP (Reclaimed Asphalt Pavement), Optimum Asphalt Levels (KAO), Asphalt Concrete - Wearing Coarse (AC – WC).